MicroRNA-21-5p Reduces Hypoxia/Reoxygenation-Induced Neuronal Cell Damage through Negative Regulation of CPEB3 - Bin Wang; Ping Yu; Wei Lin; Zhaohui Zhai (Analytical Cellular Pathology)
Objectives. To explore the role of microRNA-21-5p (miR-21-5p) in hypoxia/reoxygenation- (H/R-) induced HT22 cell damage. Methods. The hypoxia/reoxygenation (H/R) model was established in mouse neuronal cells HT22. Cell Counting Kit-8 (CCK-8) and qRT-PCR were used to determine the effects of H/R treatment on cell viability and miR-21-5p expression. HT22 cells were transfected with miR-21-5p mimic or negative control (NC) followed by the induction of H/R; cell viability, apoptosis, and SOD, MDA, and LDH activities were detected. Besides, the apoptosis-related proteins including BAX, BCL2, cleaved caspase-3, and caspase-3 as well as proteins of EGFR/PI3K/AKT signaling pathways were measured by Western blot. To verify the target relation between cytoplasmic polyadenylation element binding protein 3 (CPEB3) and miR-21-5p, luciferase reporter gene experiment was performed. After cotransfection with miR-21-5p mimic and CPEB3 plasmids, the reversal effects of CPEB3 on miR-21-5p in H/R damage were studied. Results. H/R treatment could significantly reduce the cell viability (P<0.05) and miR-21-5p levels (P<0.05) in HT22 cells. After overexpressing miR-21-5p, cell viability was increased (P<0.05) under H/R treatment, and the apoptosis rate and the levels of apoptosis-related proteins were suppressed (all P<0.05). Furthermore, SOD activity was increased (P<0.05), while MDA and LDH activity was decreased (both P<0.05). Besides, miR-21-5p could restore the activation of the EGFR/PI3K/AKT signaling pathway inhibited by H/R treatment (all P<0.05). The luciferase reporter gene experiment verified that CPEB3 is the target of miR-21-5p (P<0.05). When coexpressing miR-21-5p mimic and CPEB3 in the cells, the protective effects of miR-21-5p under H/R were reversed (all P<0.05), and the activation of the EGFR/PI3K/AKT pathway was also inhibited (all P<0.05). Conclusion. This study showed that miR-21-5p may regulate the EGFR/PI3K/AKT signaling pathway by targeting CPEB3 to reduce H/R-induced cell damage and apoptosis.